Halal Awareness, Brand Image, and Low Price Strategies on Purchasing Decisions for Food and Beverage Products - Bahri, Khoirun Nisa; Novianto, Untung; Rozak, Abdul; Gaffar, Vanessa; Wibowo, Lili Adi; Dirgantari, Puspo Dewi; Azzahra, Fanny Fatimah (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine the influence of halal awareness, brand image, and low price strategy on purchasing decisions for food and beverage products among Muslim communities in Indonesia. This research is quantitative research using a survey method for Mixue customers in West Java.Data processing uses SEM (Structural Equation Model). Data was distributed to 100 rerespondents in West Java. The results of this study conclude that the variables of Halal Awareness and Low Price Strategy have an effect on the Brand Image of Mixue products. The variables of Halal Awareness and Low Price Strategy have an effect on the purchasing decision of Mixue products. This means that the Brand Image variable can affect Halal Awareness and Low Price Strategy on the purchasing decision of Mixue products.